Efektifitas Sistem Informasi Akuntansi dengan Penerapan Omnichannel dalam Penjualan Marketplace - Mustika, Maya; Lovita, Erna; Rianto, Adi (Ma'soem University, 2024)
Along with the development of Indonesia's economy in the trading sector, information systems are highly needed for a company to achieve its goals. This research aims to determine the application and effectiveness of using accounting information systems using omnichannel systems through the Jubelio Application. The method used in this research is descriptive qualitative method with a case study of the Online Store Vape Supplies in Sunter, Tanjung Priuk. The research uses primary data with data collection techniques through observation, interviews, and documentation. The data analysis techniques used are data collection, data reduction, data presentation, and conclusion drawing. The results show that the implementation of the Jubelio application can support inventory management of the store so that the availability of stock is always updated, resulting in customer satisfaction in online transactions. Control over inventory recording runs effectively. The Jubelio application also allows integration with various shipping services on the marketplace, so customers can predict the delivery time according to their needs. In terms of information coverage, the connectivity of the Jubelio application to various marketplaces provides convenience for online store owners to expand their market share throughout Indonesia.